Trends and cyclical variation in the incidence of childhood type 1 diabetes in 26 European centres in the 25 year period 1989-2013: a multicentre prospective registration study - Patterson, Christopher C; Harjutsalo, Valma; Rosenbauer, Joachim; Neu, Andreas; Cinek, Ondrej; Skrivarhaug, Torild; Rami-Merhar, Birgit; Soltesz, Gyula; Svensson, Jannet; Parslow, Roger C; Castell, Conxa; Schoenle, Eugen J; et al. (Springer, 2019)
Against a background of a near-universally increasing incidence of childhood type 1 diabetes, recent reports from some countries suggest a slowing in this increase. Occasional reports also describe cyclical variations in incidence, with periodicities of between 4 and 6 years.